HUBUNGAN ANTARA RELIGIUSITAS DENGAN KEKAMBUHAN KLIEN SKIZOFRENIA DI POLIKLINIK JIWA RSJD DR. RM. SOEDJARWADI PROVINSI JAWA TENGAH - Nur Hidayat; Joko Mei Widiyanto (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2017)
Background: The lifetime prevalence number of schizophrenia patient in the world expand from 4  per million to 1.4 percent. Then, the prevalence number og heavy mental disorder expands as 1.7 per million. From the figure, the researcher has found that are prevalence number of metal disorder yhe Province of Central Java is 2,3 per million and the figure has been in the top three of provinces with heavy mental disorder. In relation to the finding, the researcher believes that religiosity will be able to prevent and to protect the people from the mental disorder as well as to decrease the sufferings of the mental disorder patients in order to improve the process of adaptation and recovery.Objective: The  esearcher is to understand the relationship between religiosity and recurrent in idence within the schizophrenia patients of Mental Policlinic of Soedjarwadi Hospital.Method: The research made use of analityc descriptive technique by means of cross-sectional approach. For the data gathering, the researcher made use of accidental sampling metode. The number of the sample was bivariate analysis, the researcher made use of Kendal Tau technique. Results: The results of Kendal Tau correlation test in the religiosity and recurrent incidence showed that p = 0,837 > p-value (0.05)Conclution: Based on the corrrelation test, the reseacher found that there has not been any significant correlation between religiosity and recurrent incidence within the schizophrenia patients of the Mental Polyclinic of Soedjarwadi Hospital in the central Java